Codeswitching functions in Lithuanian vlogs - Šukalova, Jekaterina (Taikomoji kalbotyra, 2025)
The aim of the present paper is to examine the phenomenon of codeswitching, namely the linguistic repertoire, the frequency, and the social functions of codeswitching appearing in the spoken language of Lithuanian vlogs – a genre that has not been researched in Lithuania at all. The analyzed vlogs cover a wide range of topics, including fashion and beauty, online entertainment, housekeeping, and agriculture. 253 instances of codeswitching were identified in the corpus of 23,562 words, suggesting a predominantly monolingual speech community in Lithuania. To determine the social motivations behind codeswitching, Appel & Muysken’s (2005) six codeswitching functions were followed. The results show that the referential function of codeswitching is used the most in the speech of Lithuanian vloggers, appearing mostly in contexts where direct equivalents of words in Lithuanian were missing. Codeswitching for expressive purposes was also frequent, appearing in contexts where speakers’ emotions and sentiments were emphasized through language use. Other functions, i.e. directive, phatic, and metalinguistic, were not numerous in use, with the poetic function of codeswitching entirely absent from the corpus.